Body atlas : the human pump : breath of life. ([S.l.] : Discovery Channel, 1996)
The Heart is a special kind of pump that circulates blood with the help of arteries, capillaries and veins and sometimes ECG's pacemakers, and heart transplat. Learn what blood pressure reveals and why blood is thicker than water.